The Evolution of Output in Transition Economies : Explaining the Differences - Sahay, Ratna (IMF Working Papers; Working Paper ;, 1999)
What are the relative roles of macroeconomic variables, structural policies, and initial conditions in explaining the time path of output in transition and the large observed differences in output performance across transition economies? Using a sample of 26 countries, this paper follows a general-to-specific modeling approach that allows for differential effects of policies and initial conditions on the private and state sectors and for time-dependent effects of initial conditions. While showing some fragility to model specification, the results point to the preeminence of structural reforms over both initial conditions and macroeconomic variables in explaining cross-country differences in performance and the timing of the recovery.